Survival Outcomes of Retreatment with Trastuzumab and Cytotoxic Chemotherapy for HER2-Positive Recurrent Patients With Breast Cancer Who Had Been Treated with Neo/adjuvant Trastuzumab Plus Multidrug Chemotherapy: A Japanese Multicenter Observational Study. (2nd July 2018) - Yamashiro, Hiroyasu; Sawaki, Masataka; Masuda, Norikazu; Okumura, Yasuhiro; Takano, Toshimi; Tokunaga, Eriko; Saito, Tsuyoshi; Sagara, Yasuaki; Yamazaki, Kosuke; Kawaguchi, Yoshihiro; Lee, Tecchuu; Ozaki, Shinji; et al.
Background: There are little data on the usefulness of trastuzumab (TZM) retreatment as the first-line treatment for patients with HER2 (human epidermal growth factor receptor 2)–positive breast cancer recurrence after perioperative treatment with TZM. Aim: To clarify the outcome and safety of TZM retreatment in patients with recurrent HER2-positive breast cancer. Method: An observational study was conducted on patients who relapsed after primary systemic therapy with TZM using the central registration system. The primary end point was progression-free survival (PFS). Secondary end points consisted of the response rate, overall survival (OS), and safety. Result: In total, 34 patients were registered between July 2009 and June 2012. The median follow-up time was 23.7 months (2-24 months). The 1- and 2-year PFS rates were 46.9% (95% confidence interval (95% CI): 29.2%-62.9%) and 29.8% (95% CI: 15.0%-46.3%), respectively (median 10.6 months). The median PFS time for patients receiving TZM combined with CTx was 13.9 months. The 1-and 2-year OR rates were 93.9 (95% CI: 77.9%-98.4%) and 84.8% (95% CI: 67.4%-93.4%). Trastuzumab-induced grade 3/4 adverse events were not observed. Conclusions: This study suggests that the PFS and OS in Japanese patients who relapsed after perioperative TZM therapy improved or were similar to those in previous reports. Differences in patient backgrounds and treatments must be considered when interpreting the results. Trastuzumab should be used combination with CTx and/or HTx for retreatment. Retreatment with TZM is safe. Trial registration: UMIN000002738.